Comparative Analysis of Supraorbital Eyebrow and Pterional Approaches for Cranio-Orbital Injury Management (Asian Journal of Pharmaceutics (AJP), 2025)
Cranio-orbital injuries are challenging craniofacial traumas because of the proximity of the orbitalcontents to vital neurovascular and ocular structures. Although the literature on orbital trauma is extensive, comparativeevidence between the supraorbital eyebrow approach (SEA) and the pterional approach (PA) in traumatic cranio-orbitalinjuries remains limited, particularly in resource-constrained settings. Materials and Methods: This retrospectivestudy evaluated the SEA and PA for treating cranio-orbital injuries in 49 patients who underwent 51 surgeries at atertiary care center in Kyrgyzstan from 2014 to 2017. The main outcomes assessed were the degree of resection, visualfunction improvement, ptosis resolution, and proptosis reduction. Secondary outcomes included cosmetic satisfaction,post-operative complications, and functional recovery, as assessed using the modified Rankin Scale. Results: The SEAwas used in 28 patients, whereas the PA was employed in 23 patients. The gross total resection rates were comparablebetween the two approaches. The SEA group reported higher cosmetic satisfaction and shorter incision lengths thanthe PA group (P < 0.05). Proptosis improved in 98.0% of cases, and visual function was enhanced in 63.2% of patientswith pre-operative impairment. Ptosis resolved in most cases, with no significant differences between the surgicalapproaches used. At ≥12 weeks follow-up, 89.2% of patients attained a modified Rankin Scale score of